Why don't you get a horse, Sam Adams? - Fritz, Jean.; Hyman, Trina Schart (New York : Coward, McCann & Geoghegan, 1974)
A brief biography of Samuel Adams describing his activities in stirring up the revolt against the British and how he was finally persuaded to learn to ride a horse.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
4.6
3-6
Keywords: Adams, Samuel, -- 1722-1803 -- Juvenile literature; Adams, Samuel, -- 1722-1803.; Adams, Samuel, -- 1722-1803.; Statesmen -- United States -- Biography; United States -- History -- Revolution, 1775-1783.; United States -- History -- 1775-1783.